Вы находитесь на странице: 1из 19

Lesson 13

Solving Definite Integrals

How to find antiderivatives


We have three methods:
1. Basic formulas
2. Algebraic simplification
3. Substitution

Basic Formulas
If f(x) is

k
cos(kx)
sin(kx)
ekx
1
x
ax

then an antiderivative is

x n +1 except if n=1
kx (assuming the variable is x!)

1
n +1

sin(kx)/k
cos(kx)/k
ekx /k

ln x
ax /ln(a)

Algebraic Simplification
2
1 3
(
x
!
1)(
x
+
1)
dx
=
x
!
1
dx
=
3 x ! x+C
"
"

! (3x + 1) dx =
2

2
3
2
9 3
6 2
9
x
+
6
x
+
1
dx
=
x
+
x
+
x
+
C
=
3
x
+
3
x
+ x+C
3
2
!

x + x2
dx =
x

x (1 + x )
dx = ! 1 + x dx = x + 12 x 2 + C
x

Integrals by Substitution
Start with
Let u=g(x).

x sin(x 2 )dx

du
= g!(x) so du = g!(x) dx
dx

Let u=?

du

u = x 2 ! du = 2xdx

1
1
1
2
2
x
sin(
x
)
dx
=
sin(
x
)
2
x
dx
=
sin(
u
)
du
=
!
cos(
x
)+C
"
"
"
2
2
2
2

Antiderivative Practice
4t
t
2sin(3t)
!
e
+
4
dt Use basic formulas:
"

Problem 1

4t
t
2
1 4t
2
sin(3t)
!
e
+
4
dt
=
!
cos(3t)
!
+
3
4 e
"

1
ln(4 )

4t + C

z 2 + 2z
dz Simplify algebraically first, then integrate.
Problem 2 !
2
z
z2 + 2z
z2 2z
2
! z 2 dz = ! z 2 + z 2 dz = ! 1 + z dz = z + 2 ln z + C
Problem 3

6t
dt
2
4+t

Make a substitution: Let u=4+t2, so du=2tdt.

6t
2t
1
2
dt
=
3
dt
=
3
du
=
3ln
u
+
C
=
3ln
4
+
t
+C
! 4 + t2
! 4 + t2
!u

Antiderivative Practice
Problem 4

2
dy Make a substitution: u=ln(ky), so du=dy/y.
y ln(ky)

2
2 1
2
dy = !
dy = ! du = 2 ln u + C = 2 ln ln(ky ) + C
y ln(ky )
ln(ky ) y
u

Problem 5 Find the particular function F(x) such that F'(x)=x2 and
the graph of F(x) passes through (1, 2).
The general antiderivative is ! x 2 dx = 13 x 3 + C
3
Then to find C, we must have F(1) = 13 1 + C = 2
Thus, C=5/3, and our function is F(x) = 13 x 3 + 53

Solving Definite Integrals


Theorem: (Fundamental Theorem I)

Or: If F is an antiderivative for f, then


Example
We determined using Simpsons Rule :
Now use the fundamental theorem:
An antiderivative for f(x)=3x + 5 is
So:

12

3x + 5 dx = F(12) - F(0) = 276 - 0 = 276

Example

x 3 dx

We have to
find an antiderivative;
evaluate at 3;
evaluate at 2;
subtract the results.

!2 x dx = x
3 3

1
4

4 3
2

= 14 3 " 14 2 =
4

This notation means:


evaluate the function at
3 and 2, and subtract the
results.

81
4

" 146 = 645 = 16.25

Dont need to include +C in our


antiderivative, because any
antiderivative will work.

Examples
"

2sin( x ) + 3x dx

3x 2
2sin( x ) + 3x dx = $2 cos x +
2

Alternate notation

=1
!

=1

"
3! 2 #
= % $2 cos ! +
$ ($2 cos 0 + 0 )
&
2 (
'
"
3! 2 #
3! 2
= % $2( $1) +
$ ($2(1) + 0 ) = 4 +
&
2 (
2
'

1
"!2 s ds
!1

1
"!2 s ds = ln s
!1

!1
!2

= ln1 ! ln 2 =!! ln 2

Practice Examples
!

1
4
dx =
e
e

3 s ds =

3s ds = 2 s
1/ 2

3/ 2

9
2

()

=2 9

3/ 2

()

"2 2

3/ 2

= 54 " 4 2

ses + 1
"!2 s ds
!1
!1
1
s
s
= " e + ds = (e + ln s ) !2 = e!1 + ln1 ! (e!2 + ln 2)
!2
s
1 1
=!! ! 2 ! ln 2
e e
!1

Substitution in Definite Integrals


We can use substitution in definite integrals.
However, the limits are in terms of the original variable.
We get two approaches:

Solve an indefinite integral first


Change the limits
Method I:
First solve an indefinite integral to find an antiderivative.
Then use that antiderivative to solve the definite integral.
Note: Do not say that a definite and an indefinite integral are equal
to each other! They cant be.

Example
First: Solve an indefinite integral.

3t
3
dt =
2
t +4
2

2t
3
dt =
2
t +4
2

u=t2+4

3t
dt
2
t +4

du= 2tdt

1
du = 32 ln t 2 + 4 + C
u
Heres an
antiderivative!

2tdt
becomes du

Pull out the 3,


and put in a 2.

Second: Use the antiderivative to solve the definite integral.

3t
dt =
2
t +4

3
2

ln t + 4
2

Heres the antiderivative


we just found.

) (
2

3
2

) (

ln 8 "

3
2

ln 5 = 23 ln 85

Example
When discussing population growth, we worked backwards to find out
what we got from evaluating

P!(t )
Lets find an antiderivative using substitution. "
dt
P (t )

"

P !(t)
dt =
P(t)

"

u= P(t)
du= P'(t)dt

1
du = ln u + C = ln P(t) + C
u

Of course, P(t) is always non-negative, so we dont need absolute


values
$ P(b) '
P !(t)
b
)
So we get: "a
dt = ln(P(t)) a = ln (P(b)) # ln (P(a)) = ln&
P(t)
% P(a) (
b

Method II: Convert the Limits


We start with x=a and x=b, and a substitution formula u=
Just put a and b into the substitution formula and get new limits.
Note: You do not have to go back to x then!
2
3t
dt Start with the same substitution
Example !1 2
t +4

u = t2 + 4
du= 2tdt

8
3t
3 2 1
3 81
3
3
8
dt
=
2
t
dt
=
du
=
ln
u
=
ln
(
)
2
2
5
!1 t 2 + 4 2 !1 t 2 + 4
5
2 !5 u
When t=1, u=5.
becomes du
becomes u
When t=2, u=8.
What happens to t=1?
And when t=2,
2
u=t2+ 4 = 1^2+4= 5. u=t + 4 = 2^2+4= 8.

Example
!

( 5 y )dy
2

( 5 y )dy = )
3

u=5y2

y= 1: u=5

du=10ydy

y=8: u= 320
4
3

1
1
320
1 8
1
1 u
y (5 y ) dy = ) (5 y 2 )3 10 y dy = ) u 3 du =
10 1
10 5
10 4
3

Note that we can also do


this problem without u-sub
--try algebraic simplification

1
2 3

320

4
4
"
3 !
= % 320 3 # 5 3 & $ 163.5
40 '
(

5y

) dy = ! y (5y )
8

1
2 3

1
5
" 1 2%
8
dy = ! $ 53 y 3 ' y dy = 53 ! y 3 dy
1
1
#
&

8
1
3

5
+1
3

1
8
8
y
3
=5
= 53 (8 3 ( 13 ) ) 163.5
5
8
+1
3
1

e4 x

Practice Example

dx

1+ e
Method I: Firstly compute
0

4x

u = 1 + e4 x
du = 4e4 x dx

e4 x
1 + e4 x

e4 x

1+ e

4x

dx
1
"
2

1
" +1
2

1
4e4 x
1 1
1
1 u
dx = !
dx = !
du = ! u du =
+C
1
4 1 + e4 x
4
4
4
u
" +1
2

1 12
1 + e4 x
= u +C =
+C
2
2

e4 x
1 + e4 x

dx =

1
1
1
1
1
1 + e4 x |10 =
1 + e4 "
1 + e0 =
1 + e4 "
2
2
2
2
2
2

u = 1 + e4 x u(0) = 1 + e4*0 = 2,u(1) = 1 + e4*1 = 1 + e4

Method II:

4x

1 + e4 x

dx =

4x

1
"
2

1
" +1
2

1 1 4e
1 1+ e 1
1 1+ e
1 u
1+ e4
dx
=
du
=
u
du
=
|
2
4 !0 1 + e4 x
4 !2
4 !2
4 1
u
" +1
2

1 12 1+ e4
1 + e4
2
= u |2 =
"
2
2
2

Using Definite Integrals


We can now evaluate many of the integrals that we have been able
to set up.
Example
Find area between y = sin(x) and the
xaxis from x=0 to x=, and from
x=0 to x=2.
The area from 0 to is clearly:

sin( x ) dx = " cos( x ) = 1 + 1 = 2


0

The area from 0 to 2 is more complicated. We note that


But this is obviously not the area!
The area from 0 to 2 can be found by:

2!

)(

2!

sin( x ) dx " # sin( x ) dx = " cos( x ) 0 + cos( x ) !


!

)= 4

"

2!

sin( x ) dx =0

Summary
Used the fundamental theorem to evaluate
definite integrals.
Made substitutions in definite integrals
By solving an indefinite integral first
By changing the limits

Used the fundamental theorem to evaluate


integrals which come from applications.